2008
DOI: 10.5194/nhess-8-1009-2008
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric conductivity effects on electrostatic field penetration into the ionosphere

Abstract: Abstract. The classic approach to calculate the electrostatic field penetration, from the Earth's surface into the ionosphere, is to consider the following equation ∇· σ ·∇ =0 whereσ and are the electric conductivity and the potential of the electric field, respectively. The penetration characteristics strongly depend on the conductivities of atmosphere and ionosphere. To estimate the electrostatic field penetration up to the orbital height of DEMETER satellite (about 700 km) the role of the ionosphere must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…The model by Pulinets et al (1998) and further modifications of that model reviewed in Pulinets et al (2003) predict an electric field of about 1 mV m −1 in the ionosphere when a 100 V m −1 vertical electric field appears near ground. The model investigated by Denisenko et al (2008) predicts in the same case much less fields, 10 µV m −1 in the night time ionosphere and 0.1 µV m −1 at day time.…”
Section: Electric Field Penetration Into the Ionospherementioning
confidence: 99%
See 4 more Smart Citations
“…The model by Pulinets et al (1998) and further modifications of that model reviewed in Pulinets et al (2003) predict an electric field of about 1 mV m −1 in the ionosphere when a 100 V m −1 vertical electric field appears near ground. The model investigated by Denisenko et al (2008) predicts in the same case much less fields, 10 µV m −1 in the night time ionosphere and 0.1 µV m −1 at day time.…”
Section: Electric Field Penetration Into the Ionospherementioning
confidence: 99%
“…Particular interest is given to the conductivity profile near the ground and the electric field distribution at the Earth's surface. Our results are discussed and compared to the models of Pulinets et al (2003) and Denisenko et al (2008). It is shown that the near ground atmospheric layer with low conductivity decreases the electric field penetration into the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations